Metafiction and Humanity in Robot: A Case Study of Thai Trilogy Novel, “You Know, The Real Literature Had To Be Written by Computer Only” by Roar-Ruea Nai Mahasamuth - Nabsib, Ornampai; Boonkachorn, Trisilpa (Journal of Letters, 2023)
This research paper aims to study metafiction and to confirm that humanity exist in robots from the beginning, rather than evolving from a robot to a human being, even though the content appears to show the development of a human being, by concentrating on an analysis of Roar-Rueanaimahasamuth’s trilogy novel, You Know, The Real Literature Had To Be Written by Computer Only. The results revealed five types of metafictions: fiction within fiction, disclosure of fiction writing process, crossing the line between the internal world and the outside world, mimicking the traditions of fiction writing and interrupting the proceedings and humanity in robots. In addition to the shape and artificial skin of the robot, they are very similar to humans. This paper proposes that robots are human from the beginning by five factors. These are feelings, memories, thinking and questioning, insubordination, and mind. These allow humans to interact with artificial intelligence as if they were humans. Humans cannot distinguish from interacting with humans or robots.